Evaluative culture and quality of educational service in the students of the faculty of education of the Universidad Nacional Mayor de San Marcos. Lima - García Gutierrez, Endira Rosario (2023)
The present research, with a quantitative approach, aims to determine how the evaluation culture is related to the quality of the educational service in the students of the Faculty of Education of the Universidad Nacional Mayor de San Marcos. Lime. The survey technique was applied to a sample, which consisted of 50 students, to whom two questionnaires were applied to measure the study variables, evaluative culture and quality of the educational service. The results obtained were analyzed at the descriptive level and at the inferential level according to the objectives and hypotheses formulated. At the descriptive level, frequencies and percentages have been used to determine the predominant levels of the study variables; At the inferential level, parametric statistics have been used, given that the data have a normal distribution and as such, Pearson's r has been used at a significance level of 0.05. The results found demonstrate that the evaluative culture is predominantly expressed at a moderate or good level, and the average level also predominates in terms of educational service. It is concluded that there is a direct and significant relationship between the evaluative culture variables and quality of educational service.